Incidental findings of Heterakis spumosa and Chirodiscoides caviae with pinworms in Sprague Dawley rats - Raslan Ain-Fatin; Saulol Hamid Nur-Fazila; Md Isa Nur-Mahiza; Abd Rahaman Yasmin; Fazil Muhammad-Azam; Hamka Nur-Kuain (Penerbit Universiti Kebangsaan Malaysia, 2020)
Endoparasites and ectoparasites have been one of the most common problems influencing the health condition of laboratory animals. The animals have a higher possibility of getting infected and their vague microbial status may alter the results of research studies. The objective of this study was to identify the presence of helminths and ectoparasites in Sprague Dawley (SD) rats and to determine the association between the type of helminths and ectoparasites infestation in two different conventionally-maintained animal facilities. A total of 60 SD rats were selected randomly. For helminths identification, perianal tape test and faecal floatation were used while ectoparasites were identified by fur pluck test. The data was analysed statistically by SPSS using the Pearson Chi-square test. In this study, pinworms; Syphacia muris and Aspiculuris tetraptera were identified in both Premise 1 and Premise 2. Out of 30 animals of each facility, 26 and 23 rats were found to be positive for helminths at each premise, respectively. Surprisingly, Heterakis spumosa that is commonly found in wild rats were identified at Premise 2. Additionally, 22 out of 30 SD rats at Premise 2 were infested heavily with Chirodiscoides caviae mites which are common in guinea pigs. The high burden of C. caviae infestation was most likely due to cross-contamination during transportation. Statistically, there was an association between the type of helminths and ectoparasites infestation in SD rats at different animal facilities (p-value=0.009). In conclusion, different practise of conventionally-maintained animal facilities influence the evidence of uncommon parasites infestation without affecting the presence of common pinworms in laboratory rats.